Pembangunan dan impak terhadap keselamatan dan kesejahteraan penduduk setempat: Analisis jaringan di Wilayah Pembangunan Iskandar Johor - Er, Ah Choy; Katiman Rostam,; Aishah@Eshah Hj. Mohamed,; Zaini Sakawi,; Abd. Rahim Md. Nor, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2009)
The impacts of developments include population growth, enhanced economic activities, usage of basic infrastructures and the exploitation of resources. This article aims to analyze the impacts of industrial development on the environment and the well-being and security of local communities’ in Iskandar Development Region (IDR). The network analysis was applied to analyze the linkages between the government, industry and society in addressing environmental issues. Secondary data were gathered from the website of IDR in Johor, the Iskandar Regional Management Office of Johor, Johor Bahru City Council and the local authorities. Primary data were gathered via face-to-face interviews based on a set of questionnaires with the local communities in November 2009 till January 2010. A total of 100 respondents selected based on cluster sampling technique were interviewed. The data collected were then analyzed via Spearman correlation analysis. The research results indicated that there was a significant relationship between environmental pollution and industrial activity (rs = 0.257, p < 0.01). Significant positive relationship were also indicated for industrial areas and high presence of foreign workers in the residential areas that are in close proximity to the industrial areas (rs = 0.217, p < 0.05). Rapid industrial developments also have an impact on the wellbeing and security of the local communities (rs = 0.249, p < 0.05). The presence of foreign workers were significantly related to social issues (rs = 0.597, p < 0.01). Thus, these social issues affect the well-being, comfort and harmony of the local communities (rs = 0.350, p < 0.01). Industrial activities and the threat to harmony amongst local communities were also significantly related (rs = 0.266, p < 0.01)